Acanthella danerii sp. nov. (Demospongiae, Bubarida, Dictyonellidae) from Chilean fjords (South Pacific Ocean) - Costa, Gabriele; Bavestrello, Giorgio; Pansini, Maurizio; Bertolino, Marco (Zootaxa, 2020)
The use of SCUBA diving for marine research in the Chilean fjords has increased the possibility of obtaining information on the sponge assemblages living in this environment. However, much work is still needed to achieve a satisfactory knowledge of the benthos of this wide region. As to sponges, just consider that seventeen new species have been recently described by several authors (Hajdu et al., 2013; Fernandez et al., 2016; Bertolino et al., 2019) with detailed information of this benthic fauna for this area. Aim of this work is the description of a new species of Acanthella (Dictyonellidae van Soest, Diaz & Pomponi, 1990), Acanthella danerii sp. nov.. It was collected at “Seno Magdalena” (44°61’48.63” S 72°95’83.12” W) (Chilean fjords) by SCUBA, at 20 m depth, on hard substrates of a vertical wall ending on a rocky bottom that slopes down to 32 m during a survey in August 2016.